PENGARUH KUALITAS AUDITOR, OPINI AUDITOR, DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG - GABRIELLA VALENTINE; MUHAMMAD ARIEF EFFENDI (E-Jurnal Akuntansi TSM, 2021)
This research aims to provide empirical evidence regarding the effect of Auditor quality, Auditor opinion, profitability, complexity of business, firm size, solvency, and audit tenure on Audit Report Lag. This research uses a sample of 165 non-financial companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period with purposive sampling as the sampling method. The data in this research were sourced from the website www.idx.co.id and used multiple regression analysis for data analysis methods. The results of this research indicate that the Auditor opinion, profitability, complexity of business, and firm size have an effect on Audit Report Lag, while Auditor quality, solvency, and audit tenure show no effect on Audit Report Lag. Auditor opinion, profitability, and firm size have a negative effect, while complexity of business has a positive effect on Audit Report Lag. The results of testing the coefficient of determination show that the independent variable in this research can only explain 11,8% of the dependent variable, which means the remaining 88,2% is explained by other variables not included in this research